Dynamic and buckling response modelling of functionally graded graphene oxide powder(GOP) reinforced cylindrical panels : Influence of GOP grading and non-uniformly, partially distributed edge loads. (June 2022) - Twinkle, C.M.; Pitchaimani, Jeyaraj
Abstract: Influence of non-uniform, partial edge loads and graded reinforcement of graphene oxide powder (GOP) on vibration and buckling behaviour of cylindrical panel is illustrated. A semi-analytical approach based on higher order shear deformation theory and Galerkin's approach is used to obtain the results. Initially, the membrane stress resultants due to the applied edge loads are developed through Airy's stress function expansion. Then the stress resultants are evaluated through the minimisation of strain energy. Followed by this, equations of motion are obtained based on Hamilton's principle and the stress resultants. Influence of loading of GOP quantity, nature of grading of GOP, nature of non-uniform and partial edge loads on critical buckling coefficient and fundamental frequency and mode shapes are investigated. It is noted that the buckling and vibration characteristics are sensitive to the nature of GOP grading, GOP loading and nature of variation in edge loads. Furthermore, the fundamental buckling mode is not always typical (1, 1) mode and (2, 1) mode is observed as the buckling mode according to the variation in aspect ratio and nature of edge loads. It is found that near critical buckling load, the fundamental vibration mode changes to (2, 1) from (1, 1) for parabolic and partial edge loading cases for the panels with aspect ratio higher than 1.3.